THE DYNAMICS OF AVERAGE ANNUAL AIR TEMPERATURE CHANGES IN THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
In the article temporal and spatial variability of average air temperature in Armenia in 1961–2012 are analyzed. The long-term measurements data of air temperature from 41 stations of national meteorological services of RA have been studied and compared with baseline period (1961–1990). A graph of the change of mean temperature is built and a map of distribution of temperature changes is compiled.
Keywords: climate change; annual temperature; baseline period; deviation